Neutrophil Lymphocyte Ratio and Acid-Fast Bacilli in Tuberculosis - Haerani Harun1 , Muhammad Nasir2 , Sumarni3, Rosa Dwi Wahyuni1 , Dita aridhatamy4 , Nur Aulia Pratiw (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Tuberculosis (TB) is one of the top 10 causes of death in the world and the most commoncause of death with single infectious agent. The neutrophil-lymphocyte ratio is a cheap and fast marker ofinflammation that has been widely studied in TB. The aimed of this study was to investigate Neutrophillymphocyte ratio (NLR) in TB with positive Acid-Fast Bacilli (AFB) and negative AFB. Methods: Thiswas a retrospective study that included TB patients data from the medical records in two hospitals in Palu,Indonesia. A total of 150 TB patients were involved in this study consisting with positive and negative AFBTB suspect. Neutrophil, lymphocyte and NLR data were compared with the Mann-Whitney test. Results:The study shows a significant difference of neutrophils and lymphocytes percentage between positive AFBTB patients (80 subjects, 53.3%) and negative AFB TB patients (70 subjects, 46.7%) with (p < 0.001) as wellas NLR (p < 0.001). The percentage of Neutrophils was significantly higher in positive AFB TB comparedto negative AFB tuberculosis (81.18 ± 8.52 vs. 55.02 ± 9.80), lymphocyte percentage were found to besignificantly lower in positive AFB TB compared with negative AFB TB (12.72 ± 7.51 vs 28.69 ± 12.01).Additionally, NLR were significantly higher in positive AFB TB compared with negative AFB TB (10.20 ±9.53 vs 2.47 ± 1.56). Conclusion: There is a significant increase in the number of neutrophils, a decrease inlymphocytes and an increase in NLR among positive AFB TB compared with negative AFB TB.